Applied Cryptography and Network Security 11th International Conference, ACNS 2013, Banff, AB, Canada, June 25-28, 2013. Proceedings - Jacobson, Michael; Locasto, Michael; Mohassel, Payman; Safavi-Naini, Reihaneh; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 11th International Conference on Applied Cryptography and Network Security, ACNS 2013, held in Banff, Canada, in June 2013. The 33 revised full papers included in this volume were carefully reviewed and selected from 192 submissions. They are organized in topical sections on Cloud Cryptography; Secure Computation; Hash Function and Block Cipher; Signature; System Attack; Secure Implementation - Hardware; Secure Implementation - Software; Group-oriented Systems; Key Exchange and Leakage Resilience; Cryptographic Proof; Cryptosystems.
Cloud Cryptography -- Secure Computation -- Hash Function and Block Cipher -- Signature -- System Attack -- Secure Implementation - Hardware -- Secure Implementation-Software -- Group-oriented Systems -- Key Exchange and Leakage Resilience -- Cryptographic Proof -- Cryptosystems.
Keywords: Computer science; Computer Communication Networks; Data protection; Data structures (Computer science).; Data encryption (Computer science).; Coding theory; Information Systems; Computer Science; Systems and Data Security; Data Encryption; Management of Computing and Information Systems; Computer Communication Networks; Coding and Information Theory; Data Structures